Dental treatment affordability and oral outcomes among U.S. adults: NHANES 2015–2018. - Alkhabbaz, Shekhah.; Altoorah, Dalal.; Al-Kandari, Abdullah.; Al-Dara'an, Hebah.; Al-Mutairi, Muna.; AlSulimmani, Woroud.; Alqedari, Hend.; Alshanbari, Mohammed.; Alhazmi, Hesham. (Tufts University. Tisch Library., 2025)
Keywords: Affordability, Cost, Oral health, DMFT..; Springer Open.